2019
DOI: 10.1038/s41598-019-41716-x
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface recombination properties in thin film semiconductors with different surface treatments from time-resolved photoluminescence measurements

Abstract: The knowledge of minority carrier lifetime of a semiconductor is important for the assessment of its quality and design of electronic devices. Time-resolved photoluminescence (TRPL) measurements offer the possibility to extract effective lifetimes in the nanosecond range. However, it is difficult to discriminate between surface and bulk recombination and consequently the bulk properties of the semiconductor cannot be estimated reliably. Here we present an approach to constrain systematically the bulk and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 31 publications
6
71
0
1
Order By: Relevance
“…These results indicate that the improvements seen are a combination of reduced back surface recombination and improved bulk absorber quality. A more detailed discussion of the TRPL behavior of these samples together with a model to estimate for the relative recombination rates at the back contact compared to the bulk recombination are shown elsewhere [20]. …”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the improvements seen are a combination of reduced back surface recombination and improved bulk absorber quality. A more detailed discussion of the TRPL behavior of these samples together with a model to estimate for the relative recombination rates at the back contact compared to the bulk recombination are shown elsewhere [20]. …”
Section: Resultsmentioning
confidence: 99%
“…The first configuration consists of a chemical bath deposited CdS buffer layer (14 min deposition) of approximately 30-nm thickness (subsequently labeled: 14Êč CdS). The CdS buffer layer has been shown to yield stable TRPL measurements [15] with a rather low front surface recombination velocity [16]. For the second configuration, the CdS layer was removed by etching the absorber in 5 wt.% HCl for 1 min (subsequently labeled: after HCl).…”
Section: Methodsmentioning
confidence: 99%
“…For the second configuration, the CdS layer was removed by etching the absorber in 5 wt.% HCl for 1 min (subsequently labeled: after HCl). It is reported that the free CIGS surface degrades in ambient air [10,17] and thus leads to an increased front surface recombination velocity [16]. The third configuration was done by a 10 wt.% KCN etch for 3 min followed by a chemical bath deposited CdS buffer layer of roughly 19 min (subsequently labeled: KCN, 19Êč CdS) of the HCl-etched absorber.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations